engaruh Metode Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Pemahaman Konsep IPA - Yulistina Nur DS; Eneng Rieza Ulfah (LPPM Universitas Buana Perjungan Karawang, 2019)
Study aims to difference the effect of Cooperative Type NHT method on understanding the science concept of Pinayungan 1 Elementary School in Telukjambe District, East Karawang Regency. This research is a type of quantitative research. The population used in this study were all fourth grade students of Pinayungan 1 Elementary School. Samples in the study were 30 students for the experimental class and 30 students for the control class. Techniques for collecting data through multiple choice tests on science subjects. Data analysis techniques used are statistical calculations. The results of testing the hypothesis, there are significant differences between the Cooperative Learning method Type Numbered head together with the results of understanding the science concept. This is obtained (t count = 3.207> t table = 2,000) with a significance of 0.05 and n = 60 indicating that the hypothesis is accepted. From the results of this study it can be concluded that there is a difference in understanding of the science concept using the Cooperative Type Numbered Head Together method.